Crossmodal links between vision and touch in covert endogenous spatial attention. - Spence, C; Pavani, F; Driver, J (2000)
The authors report a series of 6 experiments investigating crossmodal links between vision and touch in covert endogenous spatial attention. When participants were informed that visual and tactile targets were more likely on 1 side than the other, speeded discrimination responses (continuous vs. pulsed, Experiments 1 and 2; or up vs. down, Experiment 3) for targets in both modalities were significantly faster on the expected side, even though target modality was entirely unpredictable. When participants expected a target on a particular side in just one modality, corresponding shifts of covert attention also took place in the other modality, as evidenced by faster elevation judgments on that side (Experiment 4). Larger attentional effects were found when directing visual and tactile attention to the same position rather than to different positions (Experiment 5). A final study with crossed hands revealed that these visuotactile links in spatial attention apply to common positions in external space.